Edukasi Mekanisme Koping dan Spiritualitas sebagai Upaya Peningkatan Dukungan Kesehatan Jiwa pada Mahasiswa dengan Self Help Group Therapy - Fitriani, Nurlaila; Saleh, Ariyanti; Hastuti, Hastuti; Rahman, Framita; Hapsah, Hapsah; Andriani, Andriani; Meutiah, Meutiah; Febrianty, Eva; Azzahra, Nur Inaayah; Nurazizah, Nurazizah; Rasak, Risna (Universitas Baiturrahim, 2024)
The Self Help Group Therapy group for nursing students was formed as a forum for sharing stories with each other and finding solutions to problems. One intervention that can be provided is health education related to coping mechanisms and spirituality in an effort to improve mental health. The aim of this community service is to increase students' knowledge regarding coping mechanisms and spirituality. The number of participants in this service was 38 people, education and delivery of material regarding Coping Mechanisms and Spirituality was delivered by lecturers at the Faculty of Nursing, Hasanuddin University using powerpoint media in the Self Help Group Therapy group. Evaluation of implementation results regarding knowledge using a questionnaire. The results of the implementation showed that students' knowledge of coping and spiritual mechanisms found that the majority of students had increased. In conclusion, there has been an increase in students' knowledge with the Self Help Group regarding spirituality and coping mechanisms after the education was carried out. The community service team hopes that Hasanuddin University, especially the Faculty of Nursing as a partner, will be able to carry out screening to capture more students who experience mental health problems so that early prevention can be carried out and for further treatment, Self Help Group Therapy activities can be provided.